2D Boron Nitride Heterostructures: Recent Advances and Future Challenges. Issue 11 (18th August 2021) - Ren, Junkai; Innocenzi, Plinio
Abstract : Hexagonal boron nitride (h‐BN) is one of the most attractive 2D materials because of its remarkable properties. Combining h‐BN with other components (e.g., graphene, carbonitride, semiconductors) to form heterostructures opens new perspectives to developing advanced functional devices. In this review, the state‐of‐the‐art in h‐BN heterojunctions is highlighted. The preparation of high‐quality 2D h‐BN structures with fewer defects can maximize its intrinsic properties, such as thermal conductivity and electrical insulation, which are particularly important in 2D van der Waals electronics. On the other hand, the controlled introduction in 2D h‐BN of multiple defects creates new properties and advanced functions. In this last case, only through a better understanding of the nature and function of defects, it is possible to develop advanced applications based on h‐BN heterostructures. Engineering of the heterojunctions, such as the design of bonding at the interfaces, also plays a primary role. Several applications are proposed for h‐BN heterostructures, mostly in sensing and photocatalysis, and some new perspectives worth further studies are opened. Finally, the current challenges and the rising opportunities for the future developments of next‐generation h‐BN heterostructures are discussed. Abstract : The recent advances in developing functional h‐BN heterostructures are summarized in this review. The defect–properties relationship, in particular, is considered in detail together with the synthesis, functions, and potential applications. The current challenges and the rising opportunities for a successful engineering of h‐BN‐based heterojunctions are analyzed.